Some are more food secure than others - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Food Security in Sub-Saharan Africa Edited by S Devereux & S Maxwell, ITDG Publishing, 2001. 350 pp. ISBN 1853395234 GBP 15.95 Euro 25.90